NK Cell Subsets in Health and Disease: New Developments - Emanuela Marcenaro; Luigi D. Notarangelo; Jordan S. Orange; Eric Vivier (Frontiers Media SA, 2021)
Natural Killer (NK) cells were discovered ca 1975, as the first group of lymphoid cells that were neither T cells nor B cells. Since then, the dissection of the biology of NK cells has been growing exponentially with many seminal discoveries from the identification of MHC class I-specific inhibitory receptors to the discovery of receptor-ligand pairs involved in NK cell activation and to the manipulation of NK cells in cancer. In this research topic, we asked a group of thought leaders in NK cell biology to review recent advances in their origins and biology, and their roles in cancer, infection and inflammation. Together, these 25 articles provide a timely survey of NK cells as critical immunologic components of health and disease. They will hopefully prompt further dialogue and developments in basic and translational immunology.